EFEKTIVITAS APLIKASI MOKA POS DALAM MENUNJANG KINERJA KARYAWAN (Studi Kasus Pada Coffee Shop Kota Madiun) - Farista Akbar Yuliarto; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The study aims to determine the effectiveness of using the MOKA POS application in supporting employee performance. The subjects of this study were employees of Wisdom Coffee and Roastery, a coffee shop located at Jalan Captain Saputra Number 13 Madiun City. Data collection techniques using interviews. Based on the results of study, it was found that the very good category employees were able to make all menus, provide service less than or equal to 3 minutes, condition the place to be always neat with personal awareness, and arrive on time according to schedule. Meanwhile, employees in the good category are able to make 80% of the menu, provide less than or equal to 5 minutes of service, condition the place to always be neat with personal awareness, and have been late for less than 15 minutes. Employees of the moderate category are also able to make 80% of the menu but in providng service it takes more than 5 minutes, keeps the place tidy with several directions, and has been late for more than 15 minutes. From the results of interviews and attendance report data, it can be concluded that by analyzing the performance indicators of employees who use the MOKA POS application, it can determine te effectiveness of using MOKA POS to support employee performance.Keywords : Point of Sales, MOKA POS, employees performance